Respostas

2014-05-22T03:06:14-03:00
- total do que tinha: x
1ª loja) y = 1+ x/2 => y = (2+x)/2 
2ª loja) z = 1 + y/2 => (2 + y)/2 = > z = {2 + [(2+x)/2]}/2 => z = (4 + 2 + x)/2.1/2 =>
=> z = (6 + x)/4
3ª loja) h = 1 + z/2 => h = (2 + z)/2 => h = {2 +[(6+x)/4]}/2 => h = (8 + 6 + x)/4.1/2 =>    => h = (14 + x)/8
x = y + z + h
x = (2+x)/2 + (6+x)/4 + (14 + x)/8
x = [4(2+x)+2(6+x)+14 + x]/8
x = (8+4x+12+2x+14+x)/8
8x = 34 + 7x => 8x - 7x = 34 => x = 34
O homem possuía R$ 34,00 antes de entrar na primeira loja.